Study on mobile phone use while driving in a sample of Iranian drivers. Issue 2 (3rd April 2017) - Arvin, Ramin; Khademi, Mostafa; Razi-Ardakani, Hesamoddin
Abstract : The use of cell phone is a significant source of driver distraction. Phone use while driving can impair a number of factors critical for safe driving which can cause serious traffic safety problems. The objective of this paper was to investigate the frequency of using cell phones while driving in Iran's roads through an observational survey with a random sample of drivers, to recognize contributing factors to cell phone usage and to understand the magnitude of the problem. A total of 1794 observations were collected from 12 sites at controlled intersections, entrance and exit points of highways. The cell phone use rate among drivers (talking or texting) was estimated at 10% which is significantly higher than that in other countries such as Australia, USA and Canada. Rate of cell phone use among younger drivers (14.15%) was higher in comparison with other groups. In order to identify factors affecting cell phone use while driving, a binary logit model is estimated. Variables which significantly contribute to the rate of using cell phone were found to be the age of driver, number of passengers, presence of kids under the age of 8, time of observation, vehicle price and type of car.